2019
DOI: 10.1038/s41398-018-0366-5
|View full text |Cite|
|
Sign up to set email alerts
|

Stratification and prediction of remission in first-episode psychosis patients: the OPTiMiSE cohort study

Abstract: Early response to first-line antipsychotic treatments is strongly associated with positive long-term symptomatic and functional outcome in psychosis. Unfortunately, attempts to identify reliable predictors of treatment response in first-episode psychosis (FEP) patients have not yet been successful. One reason for this could be that FEP patients are highly heterogeneous in terms of symptom expression and underlying disease biological mechanisms, thereby impeding the identification of one-size-fits-all predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 77 publications
1
30
0
Order By: Relevance
“…using composite scores analyses [44], regularized regression [45], k-means clustering [26,46,47], or through a combination of unsupervised exploratory factor analysis and hierarchical clustering [48]. Consistent with our findings, the majority of these previous studies demonstrated that inflammatory profiles in patients with psychotic disorders can be sub-grouped into two main clusters, namely "high inflammatory" and a "low inflammatory" subgroups.…”
Section: Discussionsupporting
confidence: 90%
“…using composite scores analyses [44], regularized regression [45], k-means clustering [26,46,47], or through a combination of unsupervised exploratory factor analysis and hierarchical clustering [48]. Consistent with our findings, the majority of these previous studies demonstrated that inflammatory profiles in patients with psychotic disorders can be sub-grouped into two main clusters, namely "high inflammatory" and a "low inflammatory" subgroups.…”
Section: Discussionsupporting
confidence: 90%
“…They may also have increased predictive power in combination with other factors that may associate with antipsychotic response, such as clinical and demographic measures, 11–13 brain network connectivity, 74 genetic factors, 75 , 76 and blood measures. 77 We plan to address these issues in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…High inflammation before the start of treatment in both depression and schizophrenia seems to be associated with worse treatment response. A multinational, multi-center, randomized, double-blind study of first-episode psychosis patients showed that those with the most severe symptoms before treatment presented with higher pro-inflammatory compounds and were the most at risk of non-remission compared to psychosis patients with less severe symptoms (Martinuzzi et al, 2019 ). Additionally, in a longitudinal study of first-episode psychosis patients an association was found between increased high-sensitivity CRP, triglycerides and BMI at baseline, and higher PANSS scores and reduced treatment response at 1-year follow-up (Nettis et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%